ANALISIS KEPUASAN KERJA KARYAWAN PT. MITRA KARYA UTAMA PURBALINGGA DITINJAU DARI ASPEK KOMPENSASI, MOTIVASI DAN DISIPLIN - Hudaya, Zuhdan Ali; Nugroho, Adityo; Prasetyo, Agung (Faculty of Social, Economics and Humanities, 2023)
The primary objective of this study is to ascertain the impact of compensation, work motivation, and work discipline on employee job satisfaction within the context of PT Mitra Karya Tri Utama Purbalingga. This research adopts a quantitative approach, employing a simple random sampling technique to collect data via a questionnaire administered to a total of 93 respondents. The data analysis methodology encompasses descriptive statistics, instrument testing, classical assumption testing, multiple linear regression analysis, F-test, t-test, and coefficient of determination test. Upon scrutinizing the outcomes of the data analysis, it is evident that the compensation variable (X1) exhibits a partial, positive, and statistically significant influence on job satisfaction (Y), as substantiated by the t-statistic (t-count) of 2.795, surpassing the critical t-value (t-table) of 1.990. Conversely, the variables of work motivation (X2) and work discipline (X3) demonstrate no statistically significant positive influence on employee job satisfaction, as evidenced by the t-count values for work motivation (X2) at -1.559 and work discipline (X3) at -0.571, both falling below the critical t-value of 1.990. Consequently, it can be deduced that, collectively, the variables of compensation (X1), work motivation (X2), and work discipline (X3) do not exert a statistically significant positive impact on the job satisfaction (Y) of PT Mitra Karya Tri Utama Purbalingga's employees.